A novel anti-oxygen composite coating and its corrosion resistance mechanism. (June 2022) - Sun, Yue; Fu, Dengyu; Zhu, Yanji; Bai, Ziheng; Yuan, Sicheng; Chang, Yuanyuan; Meng, Lei; Wang, Huaiyuan
Abstract: To obtain environmentally friendly and highly efficient anticorrosive coatings, we elaborately designed novel filler with multiple protections. In this system, we used CeO2 nanorods modified micron-scale MMT (CeO2 &MMT) as the filler to fabricate epoxy (EP) coating at steel. For the first time, CeO2 with oxygen vacancies was designed at the MMT sheet, greatly improving the corrosion resistance of EP coating. The impedance modulus of CeO2 &MMT/EP coating maintained 10 11 Ω·cm 2 after 200 days in 3.5 wt% NaCl solution. Therefore, the work demonstrates that the novel passivation mechanism makes the CeO2 &MMT/EP coating a very promising alternative for the conventional protection system. Graphical Abstract: ga1 Highlights: Novel mixed phase cerium oxide & montmorillonite new filler is synthesized. Oxygen vacancies were formed on cerium oxide though a low temperature annealing process with good stability. Cerium oxide induces the passivation of carbon steel due to oxygen vacancies. Multiple protections greatly enhance the anti-corrosion performance of epoxy coating.